2017
DOI: 10.1186/s40560-017-0213-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term cognitive outcomes among unselected ventilated and non-ventilated ICU patients

Abstract: BackgroundCognitive dysfunction is an important long-term complication of critical illness associated with reduced quality of life, increase in healthcare costs, and institutionalization. Delirium, an acute form of brain dysfunction that is common during critical illness has been shown to be associated with long-term cognitive dysfunction. The aim of this prospective cohort study was to estimate the prevalence and severity of cognitive dysfunction in an unselected population of medical and surgical ICU patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 21 publications
1
17
1
Order By: Relevance
“…Study design and characteristics are summarized in Table 1. [11][12][13] The definition of cognitive impairment varied in different studies, and there was a wide range of neuropsychological tools used to evaluate cognitive function (Table 1). Most of the studies performed both univariate and multivariate analyses adjusted for age and severity of acute illness.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Study design and characteristics are summarized in Table 1. [11][12][13] The definition of cognitive impairment varied in different studies, and there was a wide range of neuropsychological tools used to evaluate cognitive function (Table 1). Most of the studies performed both univariate and multivariate analyses adjusted for age and severity of acute illness.…”
Section: Resultsmentioning
confidence: 99%
“…5,18 Multiple other evaluated factors were not found to influence the likelihood of post-ICU cognitive impairment, including use of sedatives and analgesic medications, extracorporeal membrane oxygenation, trophic feeding, intraoperative hypotension, and hypoxia. 12,23,[28][29][30]32 Although our study focused on the influence of potentially modifiable risk factors during critical illness on long-term cognitive impairment after discharge, it is pertinent to note that nonmodifiable factors, such as age, level of education, comorbidities, severity of illness and injury, and sepsis, can affect the risk of cognitive impairment. Age was significantly associated with long-term cognitive dysfunction in a prospective cohort study of 167 survivors of chronic critical illness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two data points were not included in the aggregate scores because they reported cognitive outcomes across multiple time points. de Azevedo and colleagues reported cognitive outcomes in the mixed population of ICU survivors at 3-18 (average, 11) months after discharge and found that half of their sample was classified as cognitively impaired on the basis of a comprehensive battery of tests (7). Similarly, Mikkelsen and colleagues (8) found that among 27 ARDS survivors, more than half were classified as cognitively impaired at variable time points up to 24 months after discharge (8).…”
Section: Frequency Of Objective Cognitive Impairment In Icu Survivorsmentioning
confidence: 99%
“…Of note, the length of delirium is the only proven risk factor for the development of long-term cognitive dysfunction so far and may also be associated with lower brain volume [10,12,14,15]. Against this, mechanical ventilation, hypoxia, sedatives, intra-operative hypotension, and use of analgesics were not associated with long-term cognitive dysfunction [16][17][18][19][20]. However, most of the previously mentioned studies did not distinguish between sepsis survivors and survivors following critical illness in general.…”
Section: Acute Phase Of Sae-deliriummentioning
confidence: 97%